Liver transplant patients have a risk of progression similar to that of sporadic patients with branch duct intraductal papillary mucinous neoplasms. Issue 12 (December 2014) - Lennon, Anne Marie; Victor, David; Zaheer, Atif; Ostovaneh, Mohammad Reza; Jeh, Jessica; Law, Joanna K.; Rezaee, Neda; Molin, Marco Dal; Ahn, Young Joon; Wu, Wenchuan; Khashab, Mouen A.; Girotra, Mohit; et al.
<x xml:space="preserve">Abstract</x> Intraductal papillary mucinous neoplasms (IPMNs) have malignant potential and can progress from low‐ to high‐grade dysplasia to invasive adenocarcinoma. The management of patients with IPMNs is dependent on their risk of malignant progression, with surgical resection recommended for patients with branch‐duct IPMN (BD‐IPMN) who develop high‐risk features. There is increasing evidence that liver transplant (LT) patients are at increased risk of extrahepatic malignancy. However, there are few data regarding the risk of progression of BD‐IPMNs in LT recipients. The aim of this study was to determine whether LT recipients with BD‐IPMNs are at higher risk of developing high‐risk features than patients with BD‐IPMNs who did not receive a transplant. Consecutive patients who underwent an LT with BD‐IPMNs were included. Patients with BD‐IPMNs with no history of immunosuppression were used as controls. Progression of the BD‐IPMNs was defined as development of a high‐risk feature (jaundice, dilated main pancreatic duct, mural nodule, cytology suspicious or diagnostic for malignancy, cyst diameter ≥3 cm). Twenty‐three LT patients with BD‐IPMN were compared with 274 control patients. The median length of follow‐up was 53.7 and 24.0 months in LT and control groups, respectively. Four (17.4%) LT patients and 45 (16.4%) controls developed high‐risk features (P = 0.99). In multivariate analysis, progression of BD‐IPMNs was associated with age at diagnosis but not with LT. There was no statistically significant difference in the risk of developing high‐risk features between the LT and the control groups. Liver Transpl 20:1462‐1467, 2014. © 2014 AASLD.